Electroconductive and free-shapeable nanocomposite hydrogels with an ultrafast self-healing property and high stretchability performance. Issue 36 (19th August 2020) - Ren, Jie; Zhao, Lingling; Zhang, Lan; Wang, Xuemiao; Li, Yan; Yang, Wu
Abstract : Conductive self-healing hydrogels as a fascinating class of materials have received much attention in recent years and been widely used in many fields. Abstract : Conductive self-healing hydrogels as a fascinating class of materials have received much attention in recent years and been widely used in many fields. However, a long healing time and poor electrical conductivity have limited their extended applications. To overcome these shortcomings, we fabricated an excellent conductive self-healing hydrogel by embedding a nanocomposite of Ag nanoparticles and reduced graphene oxide (Ag/RGO) in PVA–borax dynamic networks, which exhibits a relatively high conductivity (4.43 S m −1 ), good flexibility and excellent self-healing properties without any external stimuli. The multifunctional hydrogel could self-heal within 3 s at room temperature. It also exhibits an excellent free-shapeable property like clay such that it can be modeled into any different complex geometrical shape as desired. It is expected to have potential applications in many fields such as flexible electronic wearable devices, sensors, rechargeable batteries, and biomaterials.